49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3967
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Green Monopropellant Ignition System

Abstract: Green" propellants based on Ionic-liquids (ILs) like Ammonium DiNitramide and Hydroxyl Ammonium Nitrate have recently been developed as reduced-hazard replacements for hydrazine. Compared to hydrazine, ILs offer up to a 50% improvement in available density-specific impulse. These materials present minimal vapor hazard at room temperature, and this property makes IL's potentially advantageous for "ride-share" launch opportunities where hazards introduced by hydrazine servicing are cost-prohibitive. Even though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In 2002, Courtéoux [20] used a batch reactor to study the thermal decomposition of binary HAN/aqueous solution, and found that 60% solution concentration required energy input up to 387W/(g/s). In 2013, Stephen [21] put forward a thermal decomposition ignition scheme called "micro mixing" igniter, and successfully ignited 60% HAN solution and achieved self-sustaining combustion in 2015 [22] . In 2018, Alan [23] et al…”
Section: Japanese Research Institutions Have Carried Out Many Researc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, Courtéoux [20] used a batch reactor to study the thermal decomposition of binary HAN/aqueous solution, and found that 60% solution concentration required energy input up to 387W/(g/s). In 2013, Stephen [21] put forward a thermal decomposition ignition scheme called "micro mixing" igniter, and successfully ignited 60% HAN solution and achieved self-sustaining combustion in 2015 [22] . In 2018, Alan [23] et al…”
Section: Japanese Research Institutions Have Carried Out Many Researc...mentioning
confidence: 99%
“…The main propellant will not be ignited instantaneously after being injected into the combustion chamber, so it is necessary to calculate the cumulative mass of the combustion chamber in this delay process. The mass balance of the combustion chamber adopts the uniform vapor model [21] , that is, it is assumed that the propellant solution entering is fully atomized by the injector, expressed as vapor, and fully mixed with the products of the ignition branch. With the accumulation of propellant in the combustion chamber, the pressure in the combustion chamber has a pressure building process.…”
Section: Combustion Chamber Mass Accumulation Calculationmentioning
confidence: 99%
“…Green monopropellants (GmPs) [1] have been widely investigated as the next-generation candidates for high-performance and low-toxicity propellants. They could be used as alternatives to the conventional propellant hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, catalysts for HTP, ADN and HAN propellant blends have received a lot of attention due to an increased interest in possible replacements for hydrazine [4][5][6][7] . A particular difficulty with catalysts for ionic liquids is that a certain amount of preheating is required to initiate the decomposition process 8,9 . This has system disadvantages such as necessary heating power (typically ~10 W for a 10 N thruster) and the required time for preheating (typically 30 min), reducing the agility of the system.…”
Section: Introductionmentioning
confidence: 99%